2016
DOI: 10.1590/0100-2945-260/14
|View full text |Cite
|
Sign up to set email alerts
|

Seleção Recorrente Intrapopulacional Em Maracujazeiro-Azedo via Modelos Mistos

Abstract: RESUMO -o maracujazeiro pertence ao gênero Passiflora, considerado o de maior importância econômica da família Passifloraceae. O objetivo do trabalho foi estimar para o maracujazeiro-azedo parâmetros e valores genotípicos pelo procedimento Reml/BluP em nível de progênie. Foram avaliadas 27 progênies de meiosirmãos oriundas do segundo ciclo de seleção recorrente conduzido na uenF, selecionadas via índice de seleção. as características avaliadas foram: número de frutos por parcela (nF); massa total de frutos por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
(7 reference statements)
1
21
1
2
Order By: Relevance
“…According to Pinto et al (2013), the association between individual genotypic values obtained by REML/ BLUP and selection index was efficient at selecting individuals above the original population mean. Similarly, Pedrozo et al (2009) emphasized that the use of mixed models contributed to a greater accuracy in selection, and Ferreira et al (2016b) reported that mixed models are recommended for characteristics of low heritability, such as those obtained in the study. The SD values for severity of black-spot on leaves (BSL) and fruits (BSF) obtained by GVP was larger than that obtained by SM, which resulted in a better overall result.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Pinto et al (2013), the association between individual genotypic values obtained by REML/ BLUP and selection index was efficient at selecting individuals above the original population mean. Similarly, Pedrozo et al (2009) emphasized that the use of mixed models contributed to a greater accuracy in selection, and Ferreira et al (2016b) reported that mixed models are recommended for characteristics of low heritability, such as those obtained in the study. The SD values for severity of black-spot on leaves (BSL) and fruits (BSF) obtained by GVP was larger than that obtained by SM, which resulted in a better overall result.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, one way to increase the effectiveness of selection would be to use individual genotypic values, which are additive and have greater accuracy (RAMOS et al, 2014;QUINTAL et al, 2017). These individual genotypic values can be estimated using mixed linear models of the restricted maximum likelihood/ best linear unbiased prediction type (REML/BLUP) (FERREIRA et al, 2016b;RESENDE, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the 4 th cycle of recurrent selection, there was still a difference within the evaluated families. Ferreira et al (2016) evaluated the second cycle of recurrent selection of passion fruit of UENF and observed highmagnitude estimates of heritability within families (0.65, 0.78, and 0.67 for NF, PT, and FM, respectively), suggesting that genetic gain was greater within than among families. In this case, selection can be performed among and within families to exploit the variability and increase genetic gains.…”
Section: Genetic Parametersmentioning
confidence: 99%
“…The passion fruit belongs to the genus Passiflora, which is the most important genus in the family of Passifloraceae in the domestic fruit market (Ferreira et al, 2016). Among the species of this genus, the passion fruit (Passiflora edulis L.) is the most commonly grown for commercial purpose in Brazil (Bernacci et al, 2008).…”
Section: Introductionmentioning
confidence: 99%